Incorrect evaluation of the frequency of malnutrition and of its screening in hospitalized children by health care professionals. Issue 5 (23rd July 2015) - Restier, Lioara; Duclos, Antoine; Jarri, Laura; Touzet, Sandrine; Denis, Angelique; Occelli, Pauline; Kassai‐Koupai, Behrouz; Lachaux, Alain; Loras‐Duclaux, Irene; Colin, Cyrille; Peretti, Noel
Abstract Rationale, aims and objectives Malnutrition screening is essential to detect and to treat patients with stunting or wasting. The aim was to evaluate the subjective perception of frequency and assessment of malnutrition by health care professionals. Research methods and procedures In a paediatric university hospital, a cross‐sectional survey was conducted with a Likert scale approach to health care professionals and compared with objective measurements on a given day of frequency of malnutrition and of its screening. Results 279 health care professionals participated. The malnutrition rate, estimated versus measured, was 16.8% and 34.8%, respectively. Conversely, the estimated frequency of malnutrition screening versus measured frequency was 80.6% versus 43.1%, respectively. Furthermore, the perception of health care professionals did not differ depending on their professional category or speciality. Conclusions In conclusion, health care staff underestimates the prevalence of malnutrition in children by half and overestimates the frequency of appropriate screening practices for detection of malnutrition. This flawed/unreliable perception may disrupt both screening and the management of malnourished children. There is an urgent need to find out the reasons behind these errors caused by subjective perception in order to develop appropriate educational training to remedy the situation.